2020
DOI: 10.1016/j.cardfail.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coronavirus Disease-19 Outbreak on Physical Activity of Patients With Implantable Cardioverter Defibrillators

Abstract: Physical activity (PA) is a cornerstone of prevention to decrease mortality in patients with chronic cardiovascular disease, including heart failure. 1,2 Implantable cardiac devices offer the opportunity to monitor PA and data derived from implantable devices have been associated with shortand long-term outcomes. 3,4 During the severe acute respiratory syndrome coronavirus 2 pandemic, restrictions to outdoor activity were imposed by national authorities. In Italy, after the first case of coronavirus disease-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 8 publications
(7 reference statements)
3
20
1
Order By: Relevance
“…Eighty nine % of patients experienced this effect and a ≥ 25% relative reduction was observed for 43.3% of them. In agreement with our findings, Malanchini et al [14] showed a decrease in physical activity of more than 25% for a range of 45.9-57.2% of patients during the lockdown period. This is of utmost concern for heart failure patients considering the benefits of physical activity in primary and secondary prevention of cardiovascular disease [18].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Eighty nine % of patients experienced this effect and a ≥ 25% relative reduction was observed for 43.3% of them. In agreement with our findings, Malanchini et al [14] showed a decrease in physical activity of more than 25% for a range of 45.9-57.2% of patients during the lockdown period. This is of utmost concern for heart failure patients considering the benefits of physical activity in primary and secondary prevention of cardiovascular disease [18].…”
Section: Discussionsupporting
confidence: 94%
“…There are few studies on the effects of COVID-19 lockdown on people isolated at home for a prolonged period of time [13][14][15][16][17]. This very little literature highlighted several negative consequences of restrictive measures, such as physical inactivity, unhealthy diet, mental stress, anxiety and the resulting increased cardiovascular risk burden.…”
Section: Discussionmentioning
confidence: 99%
“…The International community is giving high priority to support cardiological practice in a setting of the disruption of previously defined protocols, and, thus, knowledge of epidemiological data is of seminal relevance 18–20 . Previous reports underscore the importance of device derived data analysis in monitoring the activity level of ICD patients, 21 the present study confirms the sensible reduction of activity level during the pandemic.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies from Italy and Japan also reported a decrease in PA [ 6 , 14 , 15 , 16 , 17 , 18 , 19 , 38 ]; or a rising prevalence of inactive older persons [ 18 , 19 ]. Despite the similarities in the mobility restriction measures among the three countries, the study populations are different: the Italian study used a cohort that underwent the implantation of a cardio meter-defibrillator before the pandemic [ 14 , 18 ] whereas the one enrolled by Suzuki et al [ 18 ] was discharged from a rehabilitation setting; both samples were significantly younger than ours. Compared with the study by Yamada et al, which showed a relevant prevalence of frailty (25%) [ 18 , 19 ], our population was older and frailer.…”
Section: Discussionmentioning
confidence: 97%
“…PA has been previously described as a risk factor for frailty [ 8 , 9 , 10 ] and a key component of interventions to prevent or reduce the development and progression of frailty [ 3 , 11 , 12 , 13 ]. It has been estimated that the preventive measures applied during the COVID-19 pandemic led to a 25% reduction of PA in the general population [ 6 , 14 , 15 , 16 , 17 ], and more than 45% in older adults [ 6 , 14 , 15 , 16 , 18 , 19 ]. Despite these data, the possible determinants of this reduction in PA levels have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%